PENGARUH BERMAIN MERONCE TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK USIA 4-5 TAHUN KELOMPOK A KECIL DI TK BAITUL MAKMUR KOTA MALANG - Ruri Lufitasari; Anik Purwati; Rani Safitri (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
The golden age of childhood is characterised by an era of fast physical and psychological development, during which the kid becomes sensitive to environmental cues and educational initiatives made both purposefully and inadvertently. Play activities like tying are one way to enhance early childhood stimulation development. To determine the effect of playing tying on fine motor development in early childhood. Research MethodeThis study's pre-experimental approach and one group pre-posttest design were employed in its design. A tiny number of people made up the study's population. a total of 20 responders, ages 4-5, at Baitul Makmur Kindergarten in Malang City. Purposive sampling was used in this study to create a sample of 18 respondents. An STPPA-style observation sheet was the instrument utilised in this investigation. The Wilcoxon test was used to analyse the data, which SPSS 16 was used to process. The Wilcoxon test research results indicate that the p value ? ? (0.05) is 0.000 <0.05, indicating the acceptance of H1 and the rejection of H0. This suggests that playing meronce has an impact on the development of fine motor skills in children between the ages of 4-5 years. Conclusion: Based on this study, it can be said that playing merging has an impact on the fine motor development of kids in small group A at Baitul Makmur Kindergarten in Malang City who are between the ages of 4 and 5.”